2019
DOI: 10.14198/jhse.2019.141.15
|View full text |Cite
|
Sign up to set email alerts
|

Improving stress coping and problem-solving skills of children in disaster-prone area through cooperative physical education and sports lesson

Abstract: The present study examined the effect of cooperative games in physical education (PE) and sports classes on the stress coping and problem-solving skills. The fifteen elementary schools in the volcano disaster area assigned to the intervention and two control groups. The intervention group received PE and sports lessons with cooperative games while the control groups completed PE and sports lessons consistent with each school's existing curriculum over 28 weeks. The stress coping and problem-solving skills scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In a previously mentioned review, Dyson et al [ 28 ] indicated that cooperative learning can promote individuals’ social and emotional learning in physical education contexts, because this pedagogical model promotes the development of social/interpersonal and emotional skills. Social learning has been more frequently researched in cooperative learning, particularly students-teachers’ connections and motivation [ 22 , 41 ], while emotional learning remains under researched. In a previous study on emotional learning variables, Luca and Tarricone [ 35 ] found that when group members have adequate emotional intelligence, two key elements in cooperative learning, positive interdependence and promotive interaction, increase.…”
Section: Introductionmentioning
confidence: 99%
“…In a previously mentioned review, Dyson et al [ 28 ] indicated that cooperative learning can promote individuals’ social and emotional learning in physical education contexts, because this pedagogical model promotes the development of social/interpersonal and emotional skills. Social learning has been more frequently researched in cooperative learning, particularly students-teachers’ connections and motivation [ 22 , 41 ], while emotional learning remains under researched. In a previous study on emotional learning variables, Luca and Tarricone [ 35 ] found that when group members have adequate emotional intelligence, two key elements in cooperative learning, positive interdependence and promotive interaction, increase.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, future work on this topic is needed. If such work demonstrates a differential effect of acute exercise and stress on working memory capacity, then effective coping strategies will need to be identified and implemented to attenuate such stress-induced working memory impairment effects [48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies were published between the years 2009 and 2022 with a maximum of publications in 2019 (five intervention studies). Duration of included studies ranged from two weeks to 28 weeks, with a mean duration of 11 weeks, excluding follow-up durations [14,15]. Overall, 18 studies were published in Europe with a maximum of eight publications from Spain.…”
Section: Characteristics Of Included Studies and Study Participantsmentioning
confidence: 99%
“…Average sample-size was 160 students, ranging from 30 to 810 participants [15,16]. Mean age ranged from 6.5 to 17.5 years with an average of 12.5 years.…”
Section: Figure 1 Prisma Flow Diagrammentioning
confidence: 99%